POLA KEPENGARANGAN DALAM MAJALAH BACA TAHUN 1974-1999 - Sri Purnomowati, Rini Yuliastuti (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2000)
The purpose of this bibliometric study is to find out authorship and citation patterns in Baca which published from 1974-1999. This study includes 81 number of publications with 151 articles. The result of the study shows that authors in Baca was dominated by male authors, except publications in 1980- 1984. Most of the authors are PDII-LIPI librarians, and the major subjects of the articles are information services, computerization/ information techno-logy, information resources, and library personnel. The authorship collaborations are low, but it has been raised for last five years. Author productivity showed the lowest since 1984-1989, but it became increase. Since 25 years of publications, the number of articles were increased, and the research paper just published at the last ten years. The most references are books, but the using of journal as references tend to grow since last ten years. The average of references are 4 documents per article which are current documents and the numbers were increased.